AN ANALYSIS OF SEMANTIC CHANGES IN JAKARTA POST - Luthfiyati, Dian; Khoirina, Najwa; Moh. Nurman; Almayda Dwi Shaputri, Zeppyca (Dialectical Literature and Educational Journal, 2024)
This study is designed to produce and provide information that will help the researcher enhance their writing skills. Changing the shape of the meaning, as seen on the online news website "Jakarta Post," is ideal because there are several types of meaning change. This study employed qualitative research methodologies to identify and describe semantic changes identified in the Jakarta Post's headlines from May to July 2021, to improve writing skills and abilities through semantic analysis. The researcher discovered all forms of semantic alterations in the Jakarta Post from May to July 2021. In data analysis, the researcher employed qualitative research methodologies to detect and describe semantic changes observed in The Jakarta Post headlines from May to July 2021, to improve writing skills and abilities. This study's population consists of all COVID-19 headlines from the Jakarta Post, which may number up to 20. Researchers found that there were three headlines of generalizations, eight headlines of specialization, one of amelioration, one of pejoration, two of synesthesia, and five of association